PENGARUH MOTIVASI KERJA DAN KOMPETENSI APARATUR TERHADAP KINERJA PELAYANAN PUBLIK DI KECAMATAN MAPANGET KOTA MANADO - Motoh, Fiolita; Laloma, Alden; Tampongangoy, Deysi (Sam Ratulangi University, 2015)
Abstract : motivation and competence of the Government apparatus work Subdistrict inGeneral still hasn't been fullestbased on background research issues aimed to measurethe influence of work motivation and competence of work on performance of public service indistrict Mapanget.In this study the methods used i.e. Survey research methods. In the methodof survey information collected fromrespondents using a questionnaire. The population inthis research is all Govt Wards and the community as much as 90people and a sample drawnin as many as 30 respondentsThe results of this study indicate the competencies and work motivation ofworking together has a positive influence on the performance of publicservice apparatus Subdistrict Mapanget, Manado city with a high degree of influence andacceptance in this research.Increasing motivation and competency work simultaneously followed by increasing theperformance of the public serviceKeywords: Motivation. Competence, Performance